Uniformity of cylindrical imploding underwater shockwaves at very small radii - Yanuka,D; Rososhek,A; Bland,SN; Krasik,YE (Applied Physics Letters, 2017)
We compare the convergent shockwaves generated from underwater, cylindrical arrays of copperwire exploded by multiple kilo-ampere current pulses on nanosecond and microsecond scales. Inboth cases, the pulsed power devices used for the experiments had the same stored energy ( 500 J)and the wire mass was adjusted to optimize energy transfer to the shockwave. Laser backlit framingimages of the shock front were achieved down to the radius of 30lm. It was found that even in thecase of initial azimuthal non-symmetry, the shock wave self-repairs in the final stages of its motion,leading to a highly uniform implosion. In both these and previous experiments, interference fringeshave been observed in streak and framing images as the shockwave approached the axis. We havebeen able to accurately model the origin of the fringes, which is due to the propagation of the laserbeam diffracting off the uniform converging shock front. The dynamics of the shockwave and itsuniformity at small radii indicate that even with only 500 J stored energies, this technique shouldproduce pressures above 10¹Pa on the axis, with temperatures and densities ideal for warm densematter research.